ESTUDO SOBRE INTERFERÊNCIAS DA MORFOLOGIA URBANA NA PERCEPÇÃO TÉRMICA HUMANA - Krüger, Eduardo; Costa, Tamiris (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Thermal perception entails to a certain extent contextual aspects which are taken into account when subjects express their thermal votes to a given indoor or outdoor space. This study concentrates on human cognition and preconceptions of thermal behavior from 3D imagery. Urban scenes have been uploaded to the Roundme 3D-image repository and a questionnaire has been used with volunteer participants who filled out online responses to questions regarding thermal perception. A differentiation of the scenes was noticed despite the absence of information regarding location, season and time of day of the scenes. Depending on the climate region respondents came from, a different relationship was noticed regarding sky openness, which reinforces the hypothesis of human cognition in studies focusing on thermal perception.